The Characteristics of Auditee and Audit Report Lag - Dodik Juliardi Iksan; Yoyok Cahyono; Popong Suryani (Jurnal Riset Akuntansi Terpadu, 2021)
The purposes of this study was to examine the effect of auditee characteristics as reflected by ROE, company size, DER and PAF’s (Public Accounting Firm) reputation on Audit Report Lag. Companies engaged in Real Estate and Property listed on the Indonesia Stock Exchange for the period 2011-2014 are used in this study. This sector was chosen because many investors are interested in investing in the real estate and property sector. The purposive sampling method was chosen as the basis for determining the sample so that a sample of 39 companies was obtained. The type of data in this study is quantitative data derived from secondary data in the form of financial reports and auditor reports which can be obtained from the page www.idx.co.id or the Indonesia Capital Market Directory (ICMD). SPSS 21 software was used to analyze research data. The results showed that ROE and company size had a significant negative effect on Audit Report Lag. DER has no effect on Audit Report Lag, while PAF's reputation has a positive effect on Audit Report Lag